2021
DOI: 10.1002/pep2.24247
|View full text |Cite
|
Sign up to set email alerts
|

Identifying blood‐brain barrier peptides by using amino acids physicochemical properties and features fusion method

Abstract: Blood-brain barrier peptides (BBPs) play a promising role in current drug study of central nervous system diseases. Hence, it is an urgent need to rapidly and accurately discriminating BBPs from non-BBPs. Experimental approaches are the first choice, however, these methods are expensive and take a lot of time. Thus, more and more researchers focused their attention on computational models. In current work, we developed a support vector machine (SVM) based model to identify BBPs. First, amino acids physicochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…These BBB-crossing peptides do not simply engage in cell membrane interaction, via AMT or RMT, but can achieve transcytosis through other distinct pathways, such as paracellular, direct diffusion or carrier-mediated transport [ 4 , 13 , 28 31 ]. However, as the main physicochemical features that allow BBB transcytosis have not been investigated in sufficient detail, researchers may rely excessively—and controversially—on analogy in assuming that CPPs are likewise able to traverse cell barriers [ 4 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…These BBB-crossing peptides do not simply engage in cell membrane interaction, via AMT or RMT, but can achieve transcytosis through other distinct pathways, such as paracellular, direct diffusion or carrier-mediated transport [ 4 , 13 , 28 31 ]. However, as the main physicochemical features that allow BBB transcytosis have not been investigated in sufficient detail, researchers may rely excessively—and controversially—on analogy in assuming that CPPs are likewise able to traverse cell barriers [ 4 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, cell-penetrating properties of peptides do not necessarily imply the ability to penetrate the BBB (Stalmans et al, 2015). Studies have demonstrated that both classes of peptides comprise different structural and physicochemical properties (de Oliveira et al, 2021;Zou, 2021). The diffusing of peptides across the BBB have been better correlated with hydrogen bonding and water desolvation than logP (Chikhale et al, 1994).…”
Section: Peptides With Penetration Into Biomembranes: Cell-penetratin...mentioning
confidence: 99%
“…Similarly, Kumar et al proposed the B3Pred, a computational tool to evaluate the prediction of the permeability of three datasets of natural and synthetic peptides that uses as molecular descriptors some structure-based properties combined with multiple ML algorithms, such as DT, RF, LR, KNN, Gaussian Naive Bayes (GNB), XGB, and SVM (Kumar et al, 2021a). Zou (2021) proposed using SVM to identify B3PPs employing physicochemical properties of the peptides. The authors used Pearson's correlation coefficient and maximal information coefficient to extract useful information to predict the permeability, which was integrated by a similarity network fusion algorithm (Zou, 2021).…”
Section: Artificial Intelligence Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similarity network fusion algorithm was utilized to integrate these two different types of features, followed by a Fisher algorithm to select the discriminative features. Finally, these selected features were input into support vector machines (SVMs) to distinguish B3PPs from non-B3PPs . However, despite the valuable information provided by these in silico methods for predicting peptide penetration of the BBB, the lack of computational tools to predict this pharmacokinetic property for both natural and chemically modified peptides hampered the efficient exploration of biotechnological and pharmaceutical applications of these molecules against several brain diseases.…”
Section: Introductionmentioning
confidence: 99%